FUNGSI HAKIM DALAM MENDORONG TERWUJUDNYA MORAL JUSTICE DALAM PERSPEKTIF ISLAM - Hamza Baharuddin (Faculty of Law, Universitas Diponegoro, 2014)
Haakim word in the dictionary which means the Arabic philosopher who describes a person who in any situation always think reflect any policy of divine creation to reap the wisdom of all creations. Judge glorified, are judges who reflect his profession as a judge, reflect on each step, contemplate every decision to be and that has dropped. Because of the decision that one's fate is at stake. Philosophical foundation of ontology justice reflect the thought process of moral justice in hasanah quranic justice filosofical.